(untitled) (Bangladesh Journal of Otorhinolaryngology, 2026)
Metastatic differentiated thyroid carcinoma that fails to respond to radioactive iodine (RAI) therapy carries a poor prognosis with frequent recurrence. Multikinase inhibitors may help slow disease progression, particularly in cases with BRAF mutations, where RAI refractoriness is common. Agents such as dabrafenib, trametinib, lenvatinib, and cabozantinib have shown therapeutic benefit. This report focuses on the clinical course of a 65 year old male with BRAF (V600E)–mutated, RAI refractory, recurrent metastatic papillary thyroid carcinoma (PTC) and his response to lenvatinib and cabozantinib.The patient initially presented with a painless anterior neck swelling, diagnosed as PTC by FNAC. CT imaging revealed subcentimetric nodal involvement, and he underwent total thyroidectomy with central compartment clearance and selective neck dissection (stageT3N1Mx). Postoperative RAI ablation (150 mCi) showed no significant uptake, though the patient remained symptom free with normal thyroglobulin and TSH levels. One year later, follow up evaluations detected metastatic cervical lymph nodes. PET CT confirmed metabolically active disease in bilateral cervical nodes and pulmonary nodules. He subsequently underwent repeat neck dissection followed by RAI, but recurrence persisted due to aggressive tumor behavior. Molecular analysis later identified a BRAF (V600E) mutation. Lenvatinib therapy was initiated to slow disease progression; however, despite partial response, the patient experienced hypertension and further nodal recurrence after multiple RAI exposures. Following additional surgery, cabozantinib was introduced, resulting in noticeable regression of metastatic neck nodes despite some adverse effects.This case highlights the aggressive nature of BRAF positive, RAI refractory PTC and underscores the therapeutic value of targeted multikinase inhibitors. Cabozantinib offered disease control in an otherwise rapidly progressive clinical scenario. This case emphasizes the importance of early molecular profiling and the role of alternative systemic therapies in managing advanced refractory thyroid carcinoma. Bangladesh J Otorhinolaryngol 2025; 31(2): 86-94